Using farmer knowledge to combat low productive spots in an irrigated rice scheme in Burkina Faso - Asten, Piet J.A. van; Barro, S.; Wopereis, Marco C.S.; Defoer, T. (Wiley, 2004)
In the oldest sections of Burkina Faso's largest irrigation scheme in the Sourou Valley (13° 10′ N, 03° 30′W) rice (Oryza sativa L.) yields dropped from about 5 to 6 t ha−1 in the early 1990s, shortly after establishment of the scheme, to 2 to 4 t ha−1 from 1995 onwards. Farmers blamed this yield decline on the appearance of 2 to 20 m diameter low productive spots. According to farmers and field measurements, the low productive spots decreased yields by 25–50 per cent. The low productive spots are caused by Zn deficiency. Low Zn availability is related to the very low DTPA‐extractable Zn content of the soil (0·08–0·46 mg kg−1), the alkaline‐calcareous character of the soil, the non‐application of Zn fertilizers, and a relatively large P fertilizer dose (21 kg P ha−1). Farmers were correct in relating the calcareous nature of the soil to the presence of the low productive spots. They were instrumental in identifying application of decomposed organic resources (e.g. rice straw at 5 t ha−1) as a short‐term solution that increases yields by 1·5 to 2·0 t ha−1. Application of Zn fertilizer (10 kg Zn ha−1) in 29 farmer fields in the 2001 dry season eradicated the low productive spots and increased yields from 3·4 to 6·0 t ha−1. Although application of Zn fertilizer is strongly recommended, it is not yet available in Burkina Faso. Based on a comparison of fertilizer prices on the world market and the local market, we expect that the use of Zn fertilizers will be highly profitable (cost/value ratio ≫ 2). Despite the relatively recent introduction of irrigated rice cropping, most farmers showed a good understanding of cropping constraints and possible solutions. Both farmers and researchers mutually benefited from each other's knowledge and observations.